Impact of Demonetization on Startup Industries in India - Mathur, Anurag; Agarwal, Himanshu (Journal of Commerce and Trade, 2019)
On 8th November 2016, Prime Minister Sh. Narendra Modi announced demonetization of Rs.500 and Rs. 1000 currency notes with a aim to target corruption, black money, terror funding and counterfeit currency. Demonetization took everyone by surprise. Many people are seen to support this bold move of Prime Minister Modi, the rest have not welcomed it with open arms. Many people are seen standing in long queues outside ATM’s, rushing to petrol pumps, rushing to the grocery stores. A start-up company is potentially feasible commercial venture which is generally a newly transpired, rapidly growing business model that focuses to achieve a market requirement by promoting or offering an innovative and extraordinary product, process or service. Startup is usually an enterprise such as a partnership, private limited company or an organization purposely designed for the rapid development of a potentially viable entrepreneurial venture. startup companies exploit technologies such as telecommunications, e-commerce, Internet, computers or robotics in a more innovative and out of the box processes of the development, validation and research for target markets. Government has taken lot of initiative to boost Startups through various supportive schemes such as Make in India, Stand up India, Pradhan Mantri Kaushal Vikas Yojna, Mudra Yojna, etc. The Banking sector has to play significant role in mounting their reach for facilitating sustainable growth in Startup sector. In this research paper the author tries to find out both positive as well as negative impact of demonetization on startup industries. Classification-JEL : E63, F18